Cross-border e-commerce marketing and managing - Hoque, Md. Rakibul; Bashaw, R. Edward, 1957- (Business Science Reference, 2021)
"This book will broaden the knowledge on the cross-border e-Commerce industry by bringing the findings and discussion on the driving forces, theoretical backgrounds, legal and logistic framework, law and taxation, trends and technology-integration and case studies pertinent to the cross-border e-Commerce industry"--